Implementing the DMA: A role for proportionality? - Monica Gambarin; George Houpis; José María Rodríguez; Tom Ovington; Juana Santamaría (International Telecommunications Society (ITS), 2023)
Now that the Digital Markets Act (DMA) will soon be implemented, different policy options can be considered, each presenting some trade-offs. In this paper we discuss the importance of taking into account proportionality when designing the specific remedies to implement the DMA. As the DMA leaves some room for different implementation options, taking into account proportionality, via an explicit framework, may help to assess the options that best accomplish the ultimate goals established in the DMA (i.e. promoting innovation, quality, fair and competitive prices and choice for end users). The proportionality framework we develop applies the principles behind telecoms regulation to horizontal interoperability in number-independent interpersonal communications services. This is the obligation set out in Article 7 in the DMA. We find that, when analysing a set of options for policy implementation through proportionality lenses, outcomes may vary considerably compared to when proportionality is neglected.
Keywords: 330